A quantification of the standing stock of macro-debris in Majuro lagoon and its effect on hard coral communities - Richards, Zoe; Beger, M. (Elsevier, 2011)
The accumulation of debris is an insidious problem throughout the world's oceans. Here we document 234.24 items of macro-debris/km2 in the shallow populated parts of Majuro lagoon (Republic of the Marshall Islands) which is the second highest standing stock of macro-debris recorded to date in any benthic marine habitat in the world. The majority of macro-debris was from household sources (78.7%) with the peak abundance recorded in areas of medium affluence. Marine debris causes suffocation, shading, tissue abrasion and mortality of corals and we show a significant negative correlation exists between the level of hard coral cover and coverage of marine debris. Given long decomposition times, even if the input of rubbish to Majuro lagoon is stopped immediately, the standing stock of debris will persist for centuries. Multiple new initiatives are needed to curtail the direct and indirect dumping of waste in Majuro lagoon. © 2011.